al-Imam Ibnu Taymiyah wa Arauhu fi al-Qadaya al-’Aqaidiyyah - Syamsul Hadi Untung; Nofriyanto Nofriyanto (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2016)
Ibnu Taimiyyah is one of the famous Muslim Scholars in Islamic history. He was also a theologian who supported the salafi movement. His Kalam thoughts are fascinating to be analyzed. Therefore, this paper will discuss Ibnu Taimiyyah’s thoughts relating to several themes on Kalam in one sides: Iman, Tawhid, Allah’s attributes, major sins, seeing Allah, al-Qur’an as His Kalam, and human actions in the world. From this simple research it comes to conclusion that Ibnu Taimiyyah agreed with Salafi scholars in the classification of Tawhid which divided into three: Tawh}i>d Rubu>biyyah, Tawh}i>d Ulu>hiyyah, Tawh}i>d asma>’ wa s}ifa>t. On another side, the discussion will be in regards to Iman, Ibnu Taimiyyah considered as iman connected to words and actions, sometimes may increase while other times it may decrease; people who have comitted major sins, Ibnu Taimiyyah saw it as a matter of judgement solely up to Allah. This idea differs from that of the Khawarij, Mu’tazilah and Murji’ah. In matter of human actions of Ibnu Taimiyyah, a human cannot be forced or coerced (laysa bi majbu>r) and also cannot freely decide independence from God, but there is the will of God within. This is different from the Jabariyah and Qadariyah view. The next aspect of the discussion covers the ability or chance to see Allah. According to Ibnu Taimiyyah, every single Mu’min will see Allah in the day of judgment which differs from the Rafidhah, Jahmiyah and Mu’tazilah view. Finally this paper will discuss the al-Qur’an as the kalam of Allah and that the al-Qur’an is not created by man.